Emerging Trends in Bioprinting for Cartilage Regeneration: Materials, Techniques and Challenges: Bioprinting for Cartilage Regeneration - Jeraj, Adam Rafiq; Zameer, Zulekha (Pakistan BioMedical Journal, 2025)
Cartilage repair is a major clinical problem because of the poor intrinsic healing capacity of cartilage coupled with the limitations of conventional therapies and synthetic substitutes. These challenges have been pursued by bioprinting, which is a technique that can generate scaffolds that mimic native cartilage. This review aims to discuss current and future development of bioprinting for cartilage tissue regeneration with a focus on the most common biomaterials such as alginate, gelatin, and collagen, along with the emerging materials such as smart hydrogels, nanomaterials, and bioactive molecules. The review also outlines other emerging bioprinting technologies like high resolution, 4D, hybrid, and microfluidic assisted bioprinting that are believed to improve the mechanical properties, biological integration and vascularization of the constructs produced through bioprinting. Some of the major problems which are still unresolved are those of scale up, biocompatibility and immune response that hinders the clinical application of bioprinted cartilage. The review further concludes that owing to some regulatory issues along with a lack of an ideal practice the challenges in bioprinting for cartilage regeneration still persists. Some of the future prospects that have been highlighted include the use of patient derived cells, artificial intelligence for process optimization and the development of smart and adaptive biomaterials. Mitigating these challenged and integrated these advanced technologies will enable the clinical translation of bioprinted cartilage to develop personalized, functional, and durable tissue constructs.